Land Reform and Peasant Marginalization in Nepal: Evaluating the 1964 Act through a Marxian Perspective (Panauti Journal, 2025)
Nepal's Land Reform Act of 1964 marked a critical juncture in the country’s transition from a feudal agrarian system to a modern developmental state. This study evaluates the socio-economic impacts of the reform on the peasantry class, particularly smallholder farmers, through a Marxian analytical lens. Drawing from secondary qualitative and quantitative data, including policy archives, empirical case studies, and scholarly critiques, this paper contends that the 1964 reform aimed to dismantle traditional landlordism but fell short in eradicating class inequality and land-based exploitation. While the reform nominally introduced tenancy rights and land ceilings, structural loopholes enabled elite landlords to retain control over large landholdings by circumventing laws through proxy ownership and kinship-based fragmentation. Moreover, the reform failed to challenge the deeply entrenched class hierarchy, reinforcing semi-feudal relations in many rural areas. Findings indicate that the reform had mixed outcomes: while some tenant farmers benefited from land titles and legal protection, others remained landless or vulnerable to informal tenancy arrangements. The research utilizes Marx’s theory of historical materialism and the class struggle to demonstrate how legal reforms, without revolutionary transformation in the ownership structure, merely reproduced existing inequalities under a new guise. The study concludes by recommending a renewed policy framework that addresses loopholes, ensures distributive justice, and centers peasant agency. This research contributes to broader discourses on agrarian transformation, state-led reforms, and postcolonial class dynamics in South Asia.